Analysis of Lithuanian Adjectives Based on Corpus Linguistics Methodology: Identification of Atypical Usage - Jancaitė-Skarbalė, Laima; Rimkutė, Erika (Taikomoji kalbotyra, 2025)
This article aims to present a study during which the usage of 94 adjectives was analyzed to identify the adjectives of atypical usage. In this research, atypical adjectives are those that differ from other adjectives in terms of their grammatical and lexical-semantic features. The adjectives were selected from the Lexical Database of Lithuanian Language Usage and analyzed using the Pedagogic Corpus of Lithuanian. In total, 12 relative and 82 qualitative adjectives were examined. The research is based on the principles of lexical grammar, which posits that words with distinct grammatical features tend to also exhibit different lexical-semantic features. The study identified 2 (16.67%) relative adjectives with atypical usage. They are relatively frequently used predicatively (e.g., paskutinis ‚last‘, vidutinis ‚average‘) and possess distinctive lexical semantic features (for example, the adjective paskutinis ‘last’ semantically resembles ordinal numerals). The analysis identified 21 (26%) qualitative adjectives with atypical usage. They were identified, first of all, according to their syntactic functions: some are relatively often used attributively (e.g., bendras ‚common‘, didis ‚great‘, didžiulis ‚huge‘, kultūringas ‚cultured‘), while others are relatively often used predicatively (e.g., aiškus ‚clear‘). These adjectives also exhibit distinctive lexical-semantic features (e.g., kultūringas can also be considered a relative adjective). Qualitative adjectives of atypical usage were also identified based on their connection abilities and gradation. Some of them do not combine with adverbs of measure/degree and cannot be graded (e.g., specialus ‚special‘); some, when used attributively in the positive degree, are relatively often used with words indicating time and place (e.g., garsus ‚famous‘, populiarus ‚popular‘, vienintelis ‚the only one‘); others are relatively often used with the dative case indicating purpose or suitability (e.g., naudingas ‚useful‘, reikalingas ‚necessary‘); some are relatively frequently used with the instrumental case (e.g., garsus ‚famous‘, ypatingas ‚special‘); others can be used with the genitive case (e.g., gausus ‚abundant‘, pilnas ‚full‘, vertas ‚worth‘); some can be used with the prepositional phrase with the preposition į ‘to’ (e.g., panašus ‘similar’); and others are used with a subordinate clause when not in the neuter gender (e.g., tikras ‚sure‘). These adjectives also tend to have distinctive lexical-semantic features (e.g., the adjective tikras ‘sure’ can function synonymously with the verb žinoti ‘to know’). Atypical usage is determined based on one or more of the features listed here.